Towards a unifying mechanism for the Hsp70 chaperones - Goloubinoff, Pierre (Henry Stewart Talks, 2007)
Hsp70s are conserved molecular chaperones, They can prevent protein aggregation, they actively unfold and solubilize aggregates and pull translocating proteins across membranes, A unifying mechanism has been proposed whereby Hsp70 uses the energy of ATP hydrolysis to recruit a force of entropic origin to locally unfold aggregates or pull proteins across membranes, Entropic pulling is a simple mechanism, reconciling earlier conflicting data, This provides a framework for curing therapies of protein misfolding diseases, Alzheimer's disease and aging
Archived at 2021/02/25